Tensions in Modern Black African Marriages – Challenges, Opportunities, and Possibilities for Leveraging Tension as a Framework for Public Pastoral Care Intervention - Magezi, Vhumani (Black theology, 2026)
The tensions in Black African marriages due to the conflict between indigenous (traditional) African marriage norms and the influence of westernisation and its consequent culture pose challenges among couples both on the African continent and in other global (diaspora) spaces. Couples are trapped in an in-between space where they oscillate between traditional marriage expectations and Western norms. In this situation, the following emerging questions are posed: What are the root causes of the tensions in modern African marriages? What pastoral care interventions can be employed to mitigate the destructive effects of these tensions and foster marriage stability and flourishing? This article employs public pastoral intervention as a practical theological hermeneutical prism to understand marriage tensions and develop a framework to guide modern African marriages. The article discusses the causes and sources of tensions in modern African marriages and proposes a public pastoral care intervention where a “tension approach” is utilised to diffuse challenges in modern African couples to promote flourishing in marriage.